Economic Literacy Research Worldwide: Insights from a Scopus Bibliometric Map - Fahmi Ashari S. Sihaloho; Fadli Agus Triansyah (Journal of Economics Education and Entrepreneurship, 2026)
Economic literacy has become increasingly strategic amid ongoing digitalization and macroeconomic uncertainty; however, its research landscape has yet to be comprehensively mapped across themes, actors, and publication channels. Method: This study employs a Scopus-based bibliometric analysis (search conducted on September 26, 2025) using the keyword “economic literacy” in titles, abstracts, and keywords. From an initial 287 records, 259 English-language documents (articles, conference papers, and reviews) were selected through relevance and inclusion–exclusion criteria. Data were analyzed using Excel, Publish or Perish, and VOSviewer to map publication trends, affiliations, sources/journals, countries, and keyword networks (co-authorship, co-citation, co-occurrence, and overlay). Results: Publications have risen sharply since 2016, peaking in 2024, with sustained activity in 2025. The Journal of Economic Education emerged as the leading outlet. Prominent affiliations originate from the United States and Europe, with strong contributions from Indonesia (notably Universitas Negeri Malang and Universitas Negeri Jakarta). The main contributing countries include the United States, Germany, Indonesia, Malaysia, and the United Kingdom. The keyword mapping reveals core clusters centered on economic literacy interlinked with financial literacy, economic education, students, and entrepreneurial intention, along with emerging themes such as digital economy, decision making, and sustainable development. Discussion/Conclusion: Economic literacy has evolved from a peripheral topic to a mainstream, increasingly interdisciplinary field. Recommendations include transparent reporting of network parameters, normalization of citation data across years, expansion of terminology and databases, and strengthening of longitudinal or quasi-experimental designs that link literacy outcomes with actual behavioral measures. Keywords: economic literacy; bibliometrics; Scopus; VOSviewer; publication trends; economic education; digital economy.